Efektivitas Keterampilan Memasang Alas Kasur Melalui Metode Modeling pada Anak Tunagrahita Ringan - Zakyatul Azizah; Kasiyati Kasiyati (Universitas Negeri Padang, 2023)
This research is motivated by the problems found in SLB Muhammadiyah Pauh IX Padang class V/C. There is one student who has a problems in the ability to set the mattress sheet. In the activity of set the mattress sheet, children have not been able to set mattress sheet neatly. Setting mattress sheet is a self-development program that trains children to be independent. To overcome this, the researchers aims to improve students' ability to set mattress sheet using the modeling method. The research method used is Single Subject Research (SSR) with an A-B-A design. This research variable improves the skills of setting mattress sheet for mild mentally retarded children. Techniques in collecting data in the form of tests and data collection tools in the form of checklist instruments. The results of data analysis carried out for 15 meetings. Based on the data obtained from the results of this study, it was shown that the modeling method is effective to improve the skills of setting mattress sheet for mild mentally retarded children at SLB Muhammadiyah Pauh IX Padang.